2006
DOI: 10.1128/ec.00068-06
|View full text |Cite
|
Sign up to set email alerts
|

Hog1 Mitogen-Activated Protein Kinase Plays Conserved and Distinct Roles in the Osmotolerant Yeast Torulaspora delbrueckii

Abstract: Torulaspora delbrueckii has emerged during evolution as one of the most osmotolerant yeasts. However, the molecular mechanisms underlying this unusual stress resistance are poorly understood. In this study, we have characterized the functional role of the high-osmolarity glycerol (HOG) mitogen-activated protein kinase pathway in mediating the osmotic stress response, among others, in T. delbrueckii. We show that the T. delbrueckii Hog1p homologue TdHog1p is phosphorylated after cell transfer to NaCl-or sorbito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 74 publications
2
9
0
Order By: Relevance
“…In the presence of the monovalent salts (NaCl and KCl), we observed the most strong and rapid HaHog1p activation within the first 60 min. A similar activation and kinetic pattern was also detected in other fungal species exposed to NaCl for the same period of time (0 to 60 min) [8] [43]. In this study, we showed that KCl, a less toxic salt compared to NaCl, can also activate the HaHOG1 pathway by phosphorylation of the HaHog1p MAPK.…”
Section: Discussionsupporting
confidence: 85%
“…In the presence of the monovalent salts (NaCl and KCl), we observed the most strong and rapid HaHog1p activation within the first 60 min. A similar activation and kinetic pattern was also detected in other fungal species exposed to NaCl for the same period of time (0 to 60 min) [8] [43]. In this study, we showed that KCl, a less toxic salt compared to NaCl, can also activate the HaHOG1 pathway by phosphorylation of the HaHog1p MAPK.…”
Section: Discussionsupporting
confidence: 85%
“…Hog1p and phospho-Hog1p were analyzed as reported(Hernandez-Lopez et al 2006) with rabbit polyclonal anti-Hog1 (y-215) (sc-9079) raised against amino acids 221-435 of Hog1p of S. cerevisiae (Santa Cruz Biotechnology, Dallas, TX) and anti-phospho-p38 MAPK (Thr180/Tyr182) respectively, diluted 1:1000 in TBS-BSA 0.5 % (w/v) and Tween 20 0.3 % (v/v). Actin was used to check the amount of protein loaded and it was detected with monoclonal anti-actin antibody (cat.…”
mentioning
confidence: 99%
“…In these fermentations, volatile acidity production remained constant throughout the entire process, in contrast with fermentation carried out by S. cerevisiae, where over 35% of the total production occurs in the initial stage of fermentation. The mechanisms of osmotic resistance in T. delbrueckii have been investigated, but are still not completely understood and are significantly different from those of S. cerevisiae (34). Survival of wine strains during the fermentation process is also imperative for their application.…”
Section: The Use Of Torulaspora Delbrueckii In the Wine Industrymentioning
confidence: 99%